Analysis of Stakeholders Participation of Competency-Based Tourism Villages Development (Case Study in Sumberbulu Tourism Village, Karanganyar Regency) - Kartika, Ratu Dika (International Journal of Social Service and Research, 2023)
The Covid-19 Pandemic condition does not undo people's intention to travel. One of them is by offering alternative tourism that provides a concept more friendly to nature and local communities, so that it becomes a trend for tourists. In order to accommodate this trend, the government is focusing on developing the potential of Tourism Villages in various parts of Indonesia, by promoting the uniqueness and local karifan. Sumberbulu Tourism Village, which is located in Sumberbulu Hamlet, Karanganyar Regency, Central Java is a strategic tourism village that must continue to be developed considering that this area is still in the priority tourist area of Borobudur. The competencies possessed by tourism human resources determine the success of tourism development in Desa Wisata Sumberbulu. A form of institutional strengthening strategy built through tourism and creative economy activities using the stakeholder participation analysis method. The impact of institutional strengthening carried out can have an influence on a stronger understanding of tourism awareness to local communities. In the end, the institutional strengthening strategy carried out succeeded in showing the relationship in tourism activities that institutionalize managers, business actors and tourists, so that the final result that is then felt is with an increase in the number of tourist visits.